Eligibility to donate blood under an individual donor assessment policy: A national cross-sectional study of gay, bisexual and other men who have sex with men in Aotearoa, New Zealand - Peter J. Saxton; Celesti Tan; Sarah Morley; Patricia Priest; Susan M. McAllister; Stephen Ritchie; Janine Paynter; Kevin Haunui; Cameron Leakey; Joseph Rich; Mark Fisher; Koson Tony Sriamporn (PLoS ONE, 2026)
Background To protect the blood supply, many countries defer higher-risk donors such as men who have had sex with men (MSM) in the last 3 months. However, this may be unnecessarily restrictive and increase non-compliance risks. New Zealand (NZ) has shifted from this approach to individual donor assessment (IDA), but the potential impact is poorly understood. We aimed to estimate the increase in blood donor eligibility and examine the characteristics of newly eligible MSM. Methods We used data from SPOTS, a large national cross-sectional online survey of MSM. Items included socio-demographics, blood donation history, views and preferences about blood donation, sexual behaviours and drug use. We described blood donation engagement and estimated the proportion eligible to donate blood under three scenarios (previous NZ policy; UK-style: IDA with chemsex deferral; Canada-style; IDA without chemsex deferral). We then examined the characteristics of potentially newly eligible MSM donors. Results Of the 3,235 participants, 43.1% had ever donated blood, 82.0% were interested in donating, 86.1% preferred an IDA-style policy, and 80.6% intended to donate, should they become eligible. We estimated 13% were eligible to donate under the previous NZ policy, rising to 37% under a UK-style IDA, and 41% under NZ’s new IDA policy. In NZ’s new IDA policy, 30% of currently ineligible participants will become eligible. Compared to participants currently eligible, newly eligible MSM were more likely to be aged 30–44 (OR 1.8, 1.4–2.4), tertiary educated (OR 1.4, 1.1–1.8), spend a lot of their free time with gay men (OR 4.3, 3.2–5.9), and identify as gay only (OR 2.5, 1.96–3.2). As expected, a high proportion of newly eligible MSM were in a regular same-sex relationship. Conclusions NZ could triple eligible MSM donors with its new IDA policy. Findings from this research are relevant internationally as blood services plan IDA implementation.